A REVIEW ON SCHEMES FOR USER AUTHENTICATION - Ghorsad, Thamraj N; Pippal, Ravi Singh (IJRDO -Journal of Computer Science Engineering, 2015)
Textual-based password evidence scheme tends to be more accessible to attacks such as shoulder surfing and hidden camera, eves dropping, dictionary attacks, social engineering. To overcome the vulnerabilities of traditional methods, graphical password schemes have been developed as possible alternative solutions to text-based password schemes. Most of the graphical schemes are accessible to shoulder surfing. To solve this problem, text can be combined with images to generate session passwords for evidence. Session passwords can be used only once and every time a new password is generated. In this paper, we introduce a new evidence techniques “authentic recallbased” and Complect recall-based techniques